Implementation of Management Functions in Arabic Language Development Programs - Taftinatul Ilmiyah; Sitti Mutmainnah; Bisri Mustofa (UII Darullughah Waddawah Pasuruan, 2026)
The increasing urgency of mastering Arabic as a key to understanding Islamic scholarly sources highlights the importance of effective management of learning programs in Islamic boarding schools. This study aims to analyze the implementation of management functions in the Arabic language development program at LPBA MUBA, including planning, organizing, actuating, and controlling, as well as their integration with Islamic boarding school values. This research uses a qualitative approach with a case study method. The subjects include administrators, tutors and students. Data were collected through non-participant observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman model through data reduction, data display, and conclusion drawing. The results show that management functions are implemented in an integrated and systematic manner. Planning is based on clear vision, mission, and task division; organizing is supported by a functional and participatory structure; implementation is conducted in stages with various learning methods; and evaluation is carried out continuously for quality control. However, challenges remain in student participation and consistency in applying the Arabic language environment The study concludes that program effectiveness is supported by structured and adaptive management based on Islamic boarding school values.